2019
DOI: 10.15171/japid.2019.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electronic cigarette liquid on monolayer and 3D tissue-engineered models of human gingival mucosa

Abstract: Background. There is limited data available on potential biological effects of E-cigarettes on human oral tissues. The aim of this study was to evaluate the effects of E-cigarette liquid on the proliferation of normal and cancerous monolayer and 3D models of human oral mucosa and oral wound healing after short-term and medium-term exposure. Methods. Normal human oral fibroblasts (NOF), immortalized OKF6-TERET-2 human oral keratinocytes, and cancerous TR146 keratinocyte monolayer cultures and 3D tissue engineer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…Our protocol includes a mixture of DMEM/F12 and KSFM, which results in a set of nutrients that yield faster growth and wound-healing recovery compared to DMEM/F12 alone. Shaikh and coworkers [84] also tested the effects of E-liquids on OKF6/TERT-2 cells and reported a decrease in viability after treatments, which agree with our results in figure 7B. Alanazi et al [85] show that the pathogenesis of yeast Candida albicans on a human gingival epithelial carcinoma cell line (grown in RPMI + 10% FBS) is increased after the microbe is exposed to tobacco flavored aerosol.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our protocol includes a mixture of DMEM/F12 and KSFM, which results in a set of nutrients that yield faster growth and wound-healing recovery compared to DMEM/F12 alone. Shaikh and coworkers [84] also tested the effects of E-liquids on OKF6/TERT-2 cells and reported a decrease in viability after treatments, which agree with our results in figure 7B. Alanazi et al [85] show that the pathogenesis of yeast Candida albicans on a human gingival epithelial carcinoma cell line (grown in RPMI + 10% FBS) is increased after the microbe is exposed to tobacco flavored aerosol.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the same cell line, cultured in Roswell Park Medical Institute (RPMI) medium + 10% FBS recovered by 24 hours after onset of the scratch in the wound-healing assay [83]. In a study by Shaikh et al, using DMEM/F12 + 10% FBS, full recovery of OKF6/TERT-2 cells took over three days [84]. This study demonstrates that cell growth with DMEM/F12 alone, even when supplied with FBS, is not as effective as KSFM or DFK.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Shaikh et al studied the effects of liquids found in electronic cigarettes on oral fibroblasts and oral keratinocytes. The authors reported that e-liquids had cytotoxic effects that depended on the concentration when cells were exposed for short to medium periods of time [ 29 ]. There are several possible mechanisms by which nicotine could cause toxicity in human keratinocytes, including the stimulation of nicotine-like acetylcholine receptors (nAChRs), thereby altering the skin’s barrier function [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the same cell line, cultured in Roswell Park Medical Institute (RPMI) medium + 10% FBS recovered by 24 hours after onset of the scratch in the wound-healing assay [86]. In a study by Shaikh et al, using DMEM/F12 + 10% FBS, full recovery of OKF6/TERT-2 cells took over three days [87]. In our hands, cells in cultured in complete DMEM/F12 without FBS (see materials and methods section 4.1), achieved full recovery within two days (Fig 3).…”
Section: Discussionmentioning
confidence: 99%